Carbon Neutrality and Sustainable Development: An Empirical Study of Indonesia’s Renewable Energy Adoption - Sari Saudi, Nur Dwiana; Abdi Reviane, Indraswati Tri; Paddu, Abdul Hamid; Agustin, Grisvia; Djam’an, Fitriwati; Sabbar, Sabbar Dahham (International Journal of Energy Economics and Policy, 2024)
In the modern world, emerging economies are examining how technological progression and carbon neutrality goals can encourage sustainable production and consumption. Striving for carbon neutrality requires using energy storage technologies and alternative energy sources. This study investigates Indonesia’s ecological sustainability, focusing on CO2 emissions and air quality index-related smog pollution, with renewable energy adoption, energy storage technology, and environmental innovation as primary influencing factors. The study employed the Quantile Autoregressive Distributed Lag (QARDL) method to explore long-term and short-term correlations between the predictors and the resultant variables. Findings reveal a significant negative correlation between adopting renewable energy (REA), using renewable energy, and EST and CO2 emissions across various quantiles in Indonesia. However, globalization was found to have a positive and significant relationship with CO2 emissions, but this association was only seen at higher quantiles. The long-term analysis revealed that environmental conservation efforts, renewable energy utilization, and environmental taxes could significantly reduce PM2.5 level haze pollution in Indonesia. The QARDL method also supports a negative long-term correlation between REA, ALT, and EST, while globalization is linked to increased CO2 emissions in Indonesia, exacerbating environmental sustainability concerns. In summary, this research concludes that practical innovation, renewable energy consumption, and environmental taxation decrease carbon emissions, while globalization increases them in Indonesia.